Voting Advice Applications and Elections - Christine Benesch; Rino L. Heim; Mark Schelker; Lukas D. Schmid (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyze how the introduction of the voting advice application (VAA) smartvote affects voter turnout, voting behavior and electoral outcomes. The Swiss context offers an ideal setting to identify the causal effects of online information with aggregate real world data because smartvote was introduced in different cantons at different points in time. In contrast to previous experimental studies, we find that smartvote did not affect turnout but that voters more actively select candidates instead of parties by splitting their ballot. Our findings suggest that no specific parties seem to benefit from the change in voting behavior and we find no effects on aggregate electoral outcomes.
Keywords: D70; D72; 330; elections; information; internet